2003
DOI: 10.1161/01.cir.0000095029.57483.60
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Cardiovascular Magnetic Resonance Predicts Reversible Myocardial Dysfunction and Remodeling in Patients With Heart Failure Undergoing β-Blocker Therapy

Abstract: Background-In some patients with heart failure, ␤-blockers can improve left ventricular (LV) function and reduce morbidity and mortality. We hypothesized that gadolinium-enhanced cardiovascular magnetic resonance imaging (CMR) can predict reversible myocardial dysfunction and remodeling in heart failure patients treated with ␤-blockers. Methods and Results-Forty-five patients with chronic heart failure underwent CMR. Contrast imaging using gadolinium was performed to obtain high-resolution spatial maps of myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
98
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(114 citation statements)
references
References 32 publications
11
98
1
3
Order By: Relevance
“…Ischemic patients’ dysfunctional viable myocardium is limited by the area of scar, which contains very little viable tissue, whereas patients with DCM have a greater area of dysfunctional viable tissue free of scar 17. Previous analyses demonstrated that the increase in LV EF is related to a higher amount of dysfunctional viable tissue before treatment,41 correlating with our findings of improvement in LV systolic function among patients with DCM.…”
Section: Discussionsupporting
confidence: 88%
“…Ischemic patients’ dysfunctional viable myocardium is limited by the area of scar, which contains very little viable tissue, whereas patients with DCM have a greater area of dysfunctional viable tissue free of scar 17. Previous analyses demonstrated that the increase in LV EF is related to a higher amount of dysfunctional viable tissue before treatment,41 correlating with our findings of improvement in LV systolic function among patients with DCM.…”
Section: Discussionsupporting
confidence: 88%
“…Since LGE indicates irreversible focal myocardial damage, even when ejection fraction is preserved,8, 9, 10 the overall low prevalence of LGE in this study represents an optimistic finding. Indeed, the CMR literature consistently indicates that LGE is associated with persistent myocardial dysfunction despite medical therapy,11, 12 arrhythmia,4, 13, 14 and in turn, adverse clinical events such as hospitalization for heart failure, arrhythmia, and mortality 4, 8, 10, 14, 15. In the setting of severe heart failure from PPCM, the low prevalence of LGE might inform decision making when contemplating advanced heart failure therapies such as mechanical circulatory support as a bridge to recovery and heart transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…While LGE can occur even when ejection fraction is preserved,8, 9, 10 LGE is generally associated with persistent myocardial dysfunction despite medical therapy,11, 12 arrhythmia,4, 13, 14 and in turn, hospitalization for heart failure, arrhythmia, and mortality 4, 8, 10, 14, 15. Regardless of etiology, LGE is prognostically adverse across the spectrum of left ventricular ejection fraction (LVEF), even when preserved 4, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators confirmed the correlation of functional recovery with transmural extent of viable tissue in acute myocardial infarction (69) as well as in chronic ischemic disease (70,71). Equally, in chronic systolic heart failure, the recovery of function after initiation of beta-blocker therapy was shown to be a measure of the transmural extent of viable myocardium (72). CMR imaging is therefore a useful tool to assess stunned as well as hibernating (73) myocardium, when functional cine imaging is combined with late enhancement imaging.…”
Section: Assessment Of Myocardial Viability In Ischemic Heart Diseasementioning
confidence: 78%